(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2024)
Hypoglycemia is a common medical problem and is mostly iatrogenic in patients with diabetes mellitus. In contrast, spontaneous hypoglycemia is relatively uncommon and poses a significant diagnostic challenge. A definitive diagnosis can be made for spontaneous hypoglycemia by using a systematic approach. After confirming the presence of a hypoglycemic disorder, a detailed history should be taken which often suggests a specific underlying cause and can guide further testing. A complete hypoglycemic blood panel must be analyzed (Plasma glucose, insulin, C-peptide, proinsulin, Beta-hydroxybutyrate, sulphonylurea screen, insulin autoantibody) during a spontaneous event or after provoked by a fasting test/mixed meal challenge test, and patients must be categorized based on their clinical status (seemingly well and unwell). J Assoc Clin Endocrinol Diabetol Bangladesh, July 2024;3(2): 58-64